1 7 2 9 [ − 1 7 2 9 ∑ 1 7 2 9 ∣ x + 1 ∣ − ∣ x − 1 ∣ ] − 1 7 2 9 [ − 1 7 2 9 ∑ 1 7 2 9 ∣ x + 1 ∣ − ∣ x ∣ ] = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Nihar Mahajan this can be done without using rule summation rule.
And you followed me Thanks. I didn't thought the man who is in the who to follow list follows me 😻😆😣I am honoured
Log in to reply
Post that method fast! Also Don't feel honoured because I am an ordinary maths lover like you who likes to share problems. Also if possible Please Like and reshare this. Thanks!
Log in to reply
@Nihar Mahajan posted It . Can you tell me your class.
Log in to reply
@A Former Brilliant Member – Yeah the solution is nice. I am in 9th STD moving to 10th.
Log in to reply
@Nihar Mahajan – Me too!! Do you have an Fb account.And please try this and like and reshare too.
Log in to reply
@A Former Brilliant Member – yes I have a fb account.I will try the problem and surely like and reshare it.
My solution is somewhat incomplete(I am a bit lazy and typing in tab is very tiresome) but my approach is clear
Log in to reply
@A Former Brilliant Member – I didnot expect this problem to be level 4.
Log in to reply
@Nihar Mahajan – Oh the level will change as more members solve it.
This way is for those who are not familiar with summation function (like me ) .
We can see that ∣ x + 1 ∣ − ∣ x − 1 ∣ is positive for all value x > 0 and negative for all values less than 0 . So we can divide the expression in two parts.
When the expression is positive we can remove modulus sign . Hence x + 1 − x + 1 = 2 which means the value of expression will 2 when x>0 . Similarly the value of expression will be -2 for all values for x<0 .At x= 0 the value will be 0. As we are asked to sum from -1729 to +1720 its value will be 1729[ 1 7 2 9 × 2 + 1 7 2 9 × − 2 + 0 ]=0
Well the first part of the equation is 0.In the second part
When x > 0 then ∣ x + 1 ∣ − ∣ x ∣ = 1 At x=0 its value is 1
When x < 0 then ∣ x + 1 ∣ − ∣ x ∣ = − x − 1 + x = − 1
So the value of second part of expression will be -1729[ 1 7 2 9 × 1 + 1 7 2 9 × − 1 + 1 ] = -1729 the answer
Problem Loading...
Note Loading...
Set Loading...
1 7 2 9 − 1 7 2 9 ∑ 1 7 2 9 ∣ x + 1 ∣ − ∣ x − 1 ∣
This is equivalent to :
1 7 2 9 × [ [ r = 0 ∑ 1 7 3 0 r + r = 0 ∑ 1 7 2 8 r ] − [ r = 0 ∑ 1 7 3 0 r + r = 0 ∑ 1 7 2 8 r ] ]
= 1 7 2 9 ( 0 ) = 0
1 7 2 9 − 1 7 2 9 ∑ 1 7 2 9 ∣ x + 1 ∣ − ∣ x ∣
This is equivalent to :
1 7 2 9 × [ [ r = 0 ∑ 1 7 3 0 r + r = 0 ∑ 1 7 2 8 r ] − [ r = 0 ∑ 1 7 2 8 r + r = 0 ∑ 1 7 2 9 r ] ]
= 1 7 2 9 ( 1 7 3 0 − 1 7 2 9 ) = 1 7 2 9 ( 1 ) = 1 7 2 9
Hence , the answer = 0 − 1 7 2 9 = − 1 7 2 9 .